The effects of stereotypes and observer pressure on athletic performance - Krendl, A.; Gainsburg, I.; Ambady, N. (Journal of Sport & Exercise Psychology, 2012)
Although the effects of negative stereotypes and observer pressure on athletic performance have been well researched, the effects of positive stereotypes on performance, particularly in the presence of observers, is not known. In the current study, White males watched a video either depicting Whites basketball players as the best free throwers in the NBA (positive stereotype), Black basketball players as the best free throwers in the NBA (negative stereotype), or a neutral sports video (control). Participants then shot a set of free throws, during which half the participants were also videotaped (observer condition), whereas the other half were not (no observer condition). Results demonstrated that positive stereotypes improved free throw performance, but only in the no observer condition. Interestingly, observer pressure interacted with the positive stereotype to lead to performance decrements. In the negative stereotype condition, performance decrements were observed both in the observer and no observer conditions.